Is Resilience in Your Life? Excerpts and Examples from my Practice - Lusted, Valerie (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change, 2011)
Developing a more resilient approach to Life’s inevitable bumps in the road is a lifestyle choice. To most, if it is nurtured, it begins to permeate both our professional and personal lives. It helps if one has daily reminders that keep the skills alive and in our foregrounds.Objectives:1. To introduce concepts related to resilience skills and abilities. 2. To provide highlights of relevant resilience research how this relates to the rehabilitation field. 3. To share highlights from staff resilience training and how this has been applied within Canada’s largest paediatric rehabilitation facility. 4. To share clinical illustrations of how the skills and abilities are applied to current practice.This article is rooted in an evidence-based resilience skills training program (known as Reaching In Reaching Out (RIRO) www.reachinginreachingout.com) designed to help adults help young children (7 years and under). By modelling resilience skills and abilities for them, children can develop a more resilient view of life. The RIRO training program uses a cognitive-behavioural and social problemsolving approach based on the Penn Resilience Program.Through music, humour, kid and family-friendly tools, narratives and other “tips”, the audience is introduced to fun and creative ways to nurture the resilience within ourselves as well as our clients/families who are coping with Life after disability. Organizational issues, implications for future research and longer term clinical applications will also be highlighted. (235)